(untitled) (Південний архів (історичні науки), 2022)
The purpose of the study is to shed light on the resistance to the Bolshevik regime in the Drabiv region in 1930, as well as to reveal the course and consequences of the Grenadier uprising based on the analysis of the oral-historical and literary sources. Methods. The groundwork of the theoretical and methodological basis of the study is a set of general scientific and purely historical methods. The generally accepted principles of objectivity, scientificity, logical-systematic and comparative analysis, problem-chronological approach, as well as methods of synthesis, generalization, processing of oral-historical sources are applied. Results and conclusions. Having studied the materials of oral history and the available literary base, we can conclude that the Drabiv uprising, like most of the peasant uprisings of that time, was caused by collectivization. The uprising actually became a civil war in the countryside, provoked by the Bolsheviks’ decision to carry out collectivization, aimed at implementing the far-reaching plans of the Soviet leadership. The Grenadier uprising was one of the first mass manifestations of dissatisfaction with the policies of the Soviet government, when the insurgents took up arms, trying to change the regime. The uprising of the Drabiv peasants had the character of spontaneous and scattered demonstrations at the level of instinctive self-defense. Of course, there was a certain organized group of educated peasants who worked out a plan for the uprising and pursued certain political motives, but there were very few of them. Most peasants defended their homes from looting by the Soviet authorities. However, the uprising was not destined to win. The struggle between well-trained DPU and police units against scattered, poorly managed and armed peasants ended in the defeat of the anti-Soviet peasant uprising. Scattered peasant demonstrations were suppressed. The outbreaks of peasant acts of disobedience were curbed by repression and, later, by the Holodomor. After all, today we can say that the Holodomor is a consequence, and one of its causes is organized uprisings during collectivization. It was the Holodomor that became a kind of weapon in the fight against overt or covert resistance. And, first of all this weapon was directed against the most conservative, most nationally conscious stratum of society – the peasantry.